PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA APLIKASI KAI ACCESS MELALUI VARIABEL INTERVENING MINAT BELI - Adi Suparwo; Aldi Priyansah; Riris Roisah (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to determine the state of Service Quality, Consumer Satisfaction, and Purchase Interest and to find out the influence of Service Quality on Consumer Satisfaction with Online Ticket Purchase Interest as an Intervening Variable in the Bandung City KAI Access Application, both partly or simultaneously. The technique used in this study is descriptive and verification with a quantitative approach. The populace used in this take look were users of the KAI Access application, totaling 100 respondents using the no-probability sampling technique, purposive sampling. The verification analysis uses path analysis. Based on The outcomes of the study, it was found that Service quality effective and extensive impact direct effect on consumer satisfaction. Service quality has an effective and extensive impact on direct effect on buying interest. Consumer pleasure has an effective and significant direct impact on buying interest, primarily based totally on the results of research that companies that provide excellent and high-satisfactory offerings without delay feel the blessings provided so that consumers can choose the quality of offerings provided by the company provides satisfaction so that it will increase buyer interest